The Issue of Freedom in Olga Sedakova’s Essays: the Intertextual Aspect - Banasiak, Daniel (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article explores Olga Sedakova’s reflection on the theme of freedom, expressed in her essayistic texts. The intertextual method of text analysis is used. The essayist interprets the meaning and value of freedom in human life relying on someone else’s word. In the analyzed essays there appear intertextual references to other texts of the Russian culture (Pushkin, Blok, Mandelshtam, Maria Petrovykh, Pasternak, Brodsky, Dmitry Prigov, Sergei Averintsev) and of the European tradition (Dante, Shakespeare, Goethe, Eluard, Schweitzer). A particular source on the basis of which Sedakova philosophizes is the Holy Scripture. She perceives the issue of freedom primarily in the poetic, moral (as the human condition) and eschatological perspective.